Sop MSDM Workshop Alat Tes Psikologi Bersama Pusat Laboratorium Dan Layanan Psikologi Fakultas Ilmu Sosial Dan Ilmu Politik - Rr. Hesti Setyodyah Lestari; Sinollah; Imron Rosyadi Hamid (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2024)
The Psychological Testing Tools Workshop is really needed for students and practitioners who work in the field of psychology and are in the educational environment. By conducting this workshop, it will increase students' potential to understand the measurement process of psychological test tools. Apart from that, we will understand how to measure, calculate scoring and the results of personality analysis. In this process, you must be careful in carrying out personality analysis because it concerns the individual's psychological condition. This is because knowing someone's personality will be difficult, both during interviews and other observation activities. One way to find out individual competence and to solve individual problems, whether regarding personal, learning or social problems, can be done by means of a psychological test. Therefore, it is very important to understand and know the rules of the psychology code of ethics which contains performance guidelines in presenting psychological test results in a valid and authentic manner